Community Decisions and Perceptions Regarding the Comfort of Living in Slum Settlements in Dalam Bugis Village - Inda Purnama; I Komang Astina; Singgih Susilo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates community decisions and perceptions regarding the comfort of living in slum settlements, specifically in Kelurahan Dalam Bugis. Amid ongoing urban development and housing challenges, understanding why residents choose to remain in environments often categorized as uninhabitable is critical. The research aims to explore the factors influencing these decisions and the subjective experiences shaping residents' sense of comfort. Utilizing a qualitative descriptive method, data were collected through in-depth interviews, observations, and documentation involving residents and local stakeholders. The findings indicate that despite infrastructural inadequacies, issues of sanitation, and high population density, many residents perceive their neighborhood as comfortable due to strong social cohesion, proximity to livelihood sources, and emotional attachment to the area. Economic limitations also play a pivotal role in shaping housing decisions. The study concludes that perceptions of comfort are not solely determined by physical conditions but are deeply intertwined with socio-economic realities and cultural values. These insights are essential for informing inclusive urban planning strategies that respect the lived experiences of marginalized urban populations.